Acupressure On Zusanli (St36) And Taibai (Sp3) in Reducing Nausea for Patients with Dyspepsia at Banyumas Hospital - Rizky Oktaviani; Mardiyono Mardiyono; Deny Achiriyati (Diponegoro University, 2015)
Background: Nausea is unpleasant sensation behind the throat and epigastrium often causing vomiting. Nausea is a major symptom in patients with dyspepsia. Typical treatments for nausea are antiemetic drugs and non-pharmacological therapy. Acupressure is a massage with finger to give stimulus at a particular point on the surface of the body. Acupressure on hand could reduce nausea in pregnant women. Purpose: The purpose of this research was to evaluate the effect of acupressure in reducing nausea for patients with dyspepsia at Banyumas hospital. Method: This research was quasi-experimental pretest-posttest control group design. The consecutive sampling technique was employed in this research with 30 subjects, 15 subjects in control and 15 subjects in intervention. In the control group received standard antiemetic drug and routine care. The intervention group was treated with acupressure Zusanli (ST 36) and Taibai (SP 3) for 30 minutes for both legs and received antiemetic drugs. Nausea was measured by Numerical Rating scale for Nausea. Data were analyzed with paired samples test and Mann Withney-U. Results: The findings show that acupressure Zusanli (ST 36) and Taibai (SP 3) for 30 minutes significantly reduced nausea in patients with dyspepsia in the intervention group (t=7.91, p=0.00) and between group (z=-2.884, p=0.01).